PEMODELAN ANGKA PORI PADA STABILISASI TANAH GAMBUT - Pradana, Mohammad Syaiful; Rohmah, Awawin Mustana (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2018)
Methods for improving peat soils to increase soil carrying capacity and reduce environmentally sound soil compressibility, namely stabilization of the peat layer. This method uses additives such as lime, fly ash and husks. This method has been developed based laboratory by civil engineers. However, it takes a relatively long time to find out the laboratory results. Therefore, research in the field of mathematical models for stabilization of peat soil was developed to predict the laboratory results. In this study, a mathematical model was derived one of the physical properties of peat soil, that is the pore number in stabilizing peat soil. The model is derived from fluid equations through porous media based on the principle of continuum and control volume. Furthermore, the model is completed using a finite difference method, the MacCormack scheme which consists of two steps, that are predictor and corrector. After the model is simulated using matlab, it is known that there is a decrease in the soil pore value to a constant condition. This decrease in pore number is due to chemical reactions that occur by additives which make the soil pores smaller. Keywords: pore number, maccormack, stabilization of peat soil